2015
DOI: 10.1007/s10689-015-9825-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of contralateral breast cancer in BRCA1 and BRCA2 mutation carriers: a 30-year semi-prospective analysis

Abstract: BRCA1 and BRCA2 mutation carriers have an increased risk of contralateral breast cancer after primary breast cancer. Risk reduction strategies are discussed after assessment of risk factors for developing contralateral breast cancer. We assessed potential risk factors that could be of use in clinical practice, including the novel use of single nucleotide polymorphisms (SNP) testing. 506 BRCA1 and 505 BRCA2 mutation carriers with a diagnosis of breast cancer were observed for up to 30 years. The risk of a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…Most previous studies reported that BRCA1 and BRCA2 mutation carriers had a 25–42% and 18–32% risk to develop CBC after 10 years of the first breast cancer among Caucasian women or Jewish, respectively . In our study, the 10‐year cumulative risk of CBC was relatively lower.…”
Section: Discussioncontrasting
confidence: 37%
See 3 more Smart Citations
“…Most previous studies reported that BRCA1 and BRCA2 mutation carriers had a 25–42% and 18–32% risk to develop CBC after 10 years of the first breast cancer among Caucasian women or Jewish, respectively . In our study, the 10‐year cumulative risk of CBC was relatively lower.…”
Section: Discussioncontrasting
confidence: 37%
“…Breast cancer patients carrying a deleterious BRCA1 or BRCA2 germline mutation have a high risk of developing primary contralateral breast cancer (CBC), with a 10‐year cumulative risk ranging from 10.8% to 42.0% . The broad range observed may be owing to the different study designs, ethnic populations and number of mutation carriers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were in line with the majority of published studies that derived the conclusion of no difference in local recurrence, 36 whereas increased incidence of CBC was associated with BRCA1/2 mutation. 4,22,[37][38][39][40][41] Till now, comprehensive research has been administrated to seek optimum prevention of CBC in BRCA mutation carriers.…”
Section: Discussionmentioning
confidence: 99%